1989
DOI: 10.1159/000120483
|View full text |Cite
|
Sign up to set email alerts
|

Current Neurosurgical Treatment of Medulloblastomas in Children

Abstract: To determine the current neurosurgical treatment of children with medulloblastomas, we reviewed the operative reports and neurosurgical report forms from 141 children with posterior fossa medulloblastomas treated on two current Children’s Cancer Study Group (CCSG) protocols, CCG-921 for high-stage and CCG-923 for low-stage medulloblastoma. Most medulloblastoma operations were performed in major medical centers: 61% of the operations were performed in CCSG member institutions, 23% in CCSG affiliates and 16% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…The strong correlation between M stage and survival has been reported for chil dren with posterior fossa PNETs (medulloblastomas), although no previous studies consist of prospectively staged patients [16], The extent of resection for children with S-PNETs was less than that previously reported for children with me dulloblastomas. Approximately 65% of patients with SPNETs had a 90% or greater resection versus 80% of patients with medulloblastomas [21]. We attribute the difference to the fact that S-PNETs are often much larger tumors than medulloblastomas, and infrequently have an intraventricular location.…”
Section: Discussionmentioning
confidence: 89%
“…The strong correlation between M stage and survival has been reported for chil dren with posterior fossa PNETs (medulloblastomas), although no previous studies consist of prospectively staged patients [16], The extent of resection for children with S-PNETs was less than that previously reported for children with me dulloblastomas. Approximately 65% of patients with SPNETs had a 90% or greater resection versus 80% of patients with medulloblastomas [21]. We attribute the difference to the fact that S-PNETs are often much larger tumors than medulloblastomas, and infrequently have an intraventricular location.…”
Section: Discussionmentioning
confidence: 89%
“…31) To achieve maximum cytoreduction, further aggressive tumor resection from the brainstem is not advised 31) and a high postoperative complication rate of up to 26% has been reported following tumor resection. 2) We performed only partial removal of the lesion because of the disappearance of the margins between the tumor and the brainstem. However, new postoperative neurological deficits related to the surgery still occurred in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The role of surgery in the treatment of medulloblasto ma has evolved with refinements in surgical techniques and improvements in instrumentation that permit more radical resection with a reduced risk of operative mortali ty and morbidity [4,10,23,24], Several earlier studies suggested that the extent of resection had prognostic impact in patients subsequently treated with craniospinal irradiation, and selected use of chemotherapy [6][7][8][9][25][26][27][28]. As a result, patients with otherwise favorable prog nostic features are now eligible for 'low-risk' treatment protocols only if there is minimal or no apparent local residual disease after initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports, like most earlier studies, have not directly addressed the importance of gross total resection in patients with medulloblastoma invading the brain stem, with or without direct extension beyond the posterior fossa (modified Chang stages T3b_4). However, some authors contend that radical surgery in such cases increases the risk of surgical morbidity, without improving local tumor control [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation